(untitled) (The Journal of Psychology and Sociology, 2015)
In the article on the basis of statistical analyzes the characteristics of the regional labor market and employment on the example of Almaty re-gion. In their study, the authors proceed from the assumption that the anal-ysis of the specificity of modern Kazakhstan society should be conducted in the context of the study of the socio-economic modernization of the region, in particular the labor market. The main research focus is on such a fundamental aspect of the labor market as employment. Also, consider-able attention is paid to the statistics and analysis of poverty in the region. Analysis of the statistics of the regional labor market and employment suggests that the region is characterized by positive dynamics, along with serious problems in the workplace. Among them: the inefficient use of time and human resources, increasing structural unemployment, low qual-ity jobs, a higher proportion of self-employed, the depreciation of human capital. The authors also drew attention to the problem of improving statistics on employment in the region. For many key indicators, determined by the situation on the labor market, statistics are not available.